Immersive technologies and language learning - Blyth, Carl (Foreign language annals, 2018)
This article briefly traces the historical conceptualization of linguistic and cultural immersion through technological applications, from the early days of locally networked computers to the cutting‐edge technologies known as virtual reality and augmented reality. Next, the article explores the challenges of immersive technologies for the field of foreign language education. Finally, a set of priority areas and research questions is posited to guide the thinking of foreign language educators over the next 50 years in their understanding of what constitutes immersion—virtual or otherwise. Challenges Immersive technologies enable new forms of experience that employ sounds and images to create engrossing simulated learning environments and allow the “real world” to merge with the digital world. How can teachers use assisted reality technology to help learners comprehend and produce a foreign language in real time?